Antistatic medical gauze and preparation method thereof
By blending carbon nanotube graphene conductive fibers, medical chitosan fibers and functional synthetic fibers, the existing anti-static medical gauze has solved the problems of unstable performance and short service life of existing anti-static medical gauzes, and achieved excellent antibacterial, breathable and anti-static properties.
Patent Information
- Application Number
- CN202411319232.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-21
AI Technical Summary
The antistatic properties of existing antistatic medical gauzes are temporarily unstable, and while improving the antistatic properties, the mechanical properties and service life are insufficient.
Using the blending technology of carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber, anti-static medical gauze with excellent antibacterial, breathable and anti-static properties is prepared through specific fiber mass ratio and process treatment.
It has achieved anti-static medical gauze with good antibacterial properties, breathability and anti-static properties, with a long service life and simple process, which is suitable for continuous and large-scale production.
Smart Images

Figure BDA0005053286600000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical gauze preparation, in particular to an antistatic medical gauze and a preparation method thereof. Background Art
[0002] Medical gauze is currently the main medical consumable for treating mild burns because of its low price and good air permeability. Medical gauze is very easy to generate static electricity during production and use. When using medical gauze under dry conditions, static electricity may be generated and accompanied by sparks. The generation of static electricity itself is harmless to the human body, but it is easy for medical gauze to absorb dust, germs, etc. in the air. In some special cases, the generation of static electricity sparks may cause damage to production equipment and cause fires and explosions of flammable items. Especially on the operating table, the generation of static electricity may cause harm to medical staff and patients. It can be seen that the development of antistatic medical gauze is imperative.
[0003] The existing method for preparing antistatic medical gauze generally involves first preparing non-functional medical gauze, then adding the medical gauze to a finishing solution containing an antistatic agent for immersion, thereby obtaining medical gauze with antistatic properties. However, although such external antistatic agents are applicable to a variety of polymers, their effectiveness is only temporary and is easily lost by subsequent contact with solvents, washing, or friction with other objects. If the antistatic properties are obtained by directly adding conductive fillers to the raw materials of the medical gauze, the mechanical properties such as the breaking strength of the obtained antistatic medical gauze will deteriorate, and the scope of application will be limited.
[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN113699788B discloses an antistatic, anti-alcohol and anti-plasma medical non-woven fabric, including the following raw materials by weight: 50 parts of PP resin, 20-40 parts of melt-blown PP material, 500-800 parts of three-anti-slurry, 20 parts of polyester fiber, 1-3 parts of organic montmorillonite, 15-20 parts of carbon fiber, 1 part of lubricant and 1 part of antioxidant; each raw material is melt-spun, hot-rolled into cloth and then impregnated with the three-anti-slurry, wherein the three-anti-slurry is obtained by polymerizing modified graphene oxide, fluorine-containing monomer, chitosan quaternary ammonium salt monomer and methyl acrylate under the action of initiator potassium persulfate, and diluting, and by adding the three-anti-slurry, the non-woven fabric is given excellent antibacterial, antistatic, anti-alcohol and anti-plasma properties, so that it can be better used in the field of medical supplies. However, its antistatic and antibacterial properties need to be further improved, and its performance stability needs to be further improved.
[0005] It can be seen that the development of an antistatic medical gauze with good antibacterial properties, excellent air permeability and antistatic properties, and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the medical gauze field. Summary of the invention
[0006] In view of the above problems, the object of the present invention is to provide an antistatic medical gauze with good antibacterial property, excellent air permeability and antistatic performance, and long service life, and a preparation method thereof.
[0007] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: an antistatic medical gauze, which is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:(0.3-0.5):0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer, (3,6-diamino-9-acridinyl)boric acid 3-5 parts; the functional synthetic copolymer includes structural units introduced by the following monomers: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0008] Preferably, the preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and an initiator to a high boiling point solvent, stirring and reacting at 60-70° C. in an inert gas atmosphere for 3-6 hours, then precipitating in water, washing the precipitated polymer with water for 3-6 times, and finally drying in a vacuum drying oven at 85-95° C. to constant weight to obtain a functional synthetic copolymer.
[0009] Preferably, the mass ratio of the 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:(1-3):(0.8-1.2):(1-2):(0.1-0.3):(0.05-0.08):(15-30).
[0010] Preferably, the initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
[0011] Preferably, the preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, and then adding it into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 55-65°C, soaking for 15-25 hours, washing with clean water, and then drying to make the functional synthetic fiber.
[0012] Preferably, the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 5-12 wt %.
[0013] Preferably, the process parameters of the melt spinning are: spinning temperature 210-230° C., winding speed 500-1200 m / min, and draft ratio 3.2-4.2.
[0014] Preferably, the carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filament, and is provided by Zhejiang Rifang Nano Biotechnology Co., Ltd.
[0015] Preferably, the medical chitosan fiber has a thickness of 2D, a fiber shape of filament, a brand of Yingjia Ke 100, a product number of CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0016] Another object of the present invention is to provide a method for preparing the antistatic medical gauze, comprising the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling and bleaching combined machine, with a bath ratio of 1: (25-30), first washing with 95-100° C. water for 20-30 minutes, then lowering the temperature by 5-10° C. and washing with water for 4-8 minutes; taking out the cloth, dehydrating it with a dehydrator for 20-25 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 108-132° C. for 16-26 minutes to obtain the antistatic medical gauze.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The preparation method of the antistatic medical gauze disclosed in the present invention does not require special equipment, has a simple process flow, is convenient to operate and control, has high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.
[0019] (2) The antistatic medical gauze disclosed in the present invention is a blend of carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber is 0.4:(0.3-0.5):0.6; the advantages of the three fiber materials are combined, so that the prepared medical gauze has good antibacterial property, excellent air permeability and antistatic performance, and long service life. The functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer, 3-5 parts of (3,6-diamino-9-acridinyl) boric acid; the functional synthetic copolymer includes structural units introduced by the following monomers: 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione. The imidazole salt, oxazolidinone, amphoteric organic ion salt, cyano trifluoromethylphenyl and triazone group are introduced simultaneously. Under the multiple effects of electronic effect, steric effect and conjugation effect, these groups can give the product better antibacterial, breathable and antistatic properties, and better performance stability.
[0020] (3) The antistatic medical gauze disclosed in the present invention comprises a functional synthetic fiber soaked in an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid, wherein the boric acid group on the (3,6-diamino-9-acridinyl)boric acid can undergo ion exchange with the imidazole salt on the functional synthetic copolymer, and at the same time, the amino group on the (3,6-diamino-9-acridinyl)boric acid can undergo epoxy ring-opening reaction with the epoxy group on the functional synthetic copolymer, thereby forming an interpenetrating network structure on the surface of the functional synthetic fiber. At the same time, an acridine structure is introduced, which works together with other groups to effectively improve the performance stability of the gauze. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0022] Example 1
[0023] An antistatic medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:0.3:0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer and 3 parts of (3,6-diamino-9-acridinyl)boric acid; the functional synthetic copolymer comprises The structural units introduced by the following monomers are included: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0024] The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting at 60°C for 3h in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with water for 3 times, and finally drying in a vacuum drying oven at 85°C to constant weight to obtain the functional synthetic copolymer. The copolymer is synthesized; the mass ratio of 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:1:0.8:1:0.1:0.05:15; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; the inert gas is nitrogen; the M of the functional synthetic copolymer is measured by GPC test. n =15351 g / mol, M W / M n=1.379; calculated by elemental analysis and weight change, the mass ratio of the structural units introduced by 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in the functional synthetic copolymer is 0.99:1:0.78:0.98.
[0025] The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding the copolymer into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 55°C, soaking for 15 hours, washing with clean water, and drying to prepare the functional synthetic fiber; the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 5wt%; the process parameters of the melt spinning are: spinning temperature of 210°C, winding speed of 500m / min, and drafting multiple of 3.2.
[0026] The carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filaments, and is provided by Zhejiang Rifang Nanobiotechnology Co., Ltd.; the medical chitosan fiber has a thickness of 2D and a fiber shape of filaments, the brand is Yingjia Ke 100, the item number is CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0027] A preparation method of the antistatic medical gauze comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:25, first washing with 95°C water for 20 minutes, then lowering the temperature by 5°C and washing with water for 4 minutes; taking out the cloth, dehydrating it with a dehydrator for 20 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 108°C for 16 minutes to obtain the antistatic medical gauze.
[0028] Example 2
[0029] An antistatic medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:0.35:0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer, 3.5 parts of (3,6-diamino-9-acridinyl) boric acid; the functional synthetic copolymer The compound includes structural units introduced by the following monomers: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0030] The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting at 63°C for 4 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with water for 4 times, and finally drying in a vacuum drying oven at 87°C to constant weight. A functional synthetic copolymer is obtained; the mass ratio of 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:1.5:0.9:1.2:0.15:0.06:18; the initiator is azobisisobutyronitrile; the high boiling point solvent is N,N-dimethylformamide; and the inert gas is helium.
[0031] The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding the copolymer into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 58°C, soaking for 18 hours, washing with clean water, and drying to prepare the functional synthetic fiber; the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 8wt%; the process parameters of the melt spinning are: spinning temperature of 215°C, winding speed of 700m / min, and drafting multiple of 3.5.
[0032] The carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filaments, and is provided by Zhejiang Rifang Nanobiotechnology Co., Ltd.; the medical chitosan fiber has a thickness of 2D and a fiber shape of filaments, the brand is Yingjia Ke 100, the item number is CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0033] A preparation method of the antistatic medical gauze comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:26, first washing with 97°C water for 23 minutes, then lowering the temperature by 6°C and washing with water for 5 minutes; taking out the cloth, dehydrating it with a dehydrator for 22 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 115°C for 18 minutes to obtain the antistatic medical gauze.
[0034] Example 3
[0035] An antistatic medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:0.4:0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer and 4 parts of (3,6-diamino-9-acridinyl)boric acid; the functional synthetic copolymer comprises The structural units introduced by the following monomers are included: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0036] The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting at 65°C for 4.5 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with water for 5 times, and finally drying in a vacuum drying oven at 90°C. to constant weight to obtain a functional synthetic copolymer; the mass ratio of 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:2:1:1.5:0.2:0.065:23; the initiator is azobisisobutyronitrile; the high boiling point solvent is N-methylpyrrolidone; and the inert gas is neon.
[0037] The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding the copolymer into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 60°C, soaking for 20 hours, washing with clean water, and drying to prepare the functional synthetic fiber; the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 9wt%; and the process parameters of the melt spinning are: spinning temperature of 220°C, winding speed of 900m / min, and drafting multiple of 3.8.
[0038] The carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filaments, and is provided by Zhejiang Rifang Nanobiotechnology Co., Ltd.; the medical chitosan fiber has a thickness of 2D and a fiber shape of filaments, the brand is Yingjia Ke 100, the item number is CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0039] A preparation method of the antistatic medical gauze comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:28, first washing with 98°C water for 25 minutes, then lowering the temperature by 8°C and washing with water for 6 minutes; taking out the cloth, dehydrating it with a dehydrator for 23 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 123°C for 23 minutes to obtain the antistatic medical gauze.
[0040] Example 4
[0041] An antistatic medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:0.45:0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer, 4.5 parts of (3,6-diamino-9-acridinyl) boric acid; the functional synthetic copolymer The compound includes structural units introduced by the following monomers: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0042] The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting at 68°C in an inert gas atmosphere for 5.5 hours, then precipitating in water, washing the precipitated polymer with water for 6 times, and finally drying in a vacuum drying oven at 93°C to constant weight to obtain the functional synthetic copolymer; -allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent are in a mass ratio of 1:2.5:1.1:1.8:0.25:0.075:28; the initiator is azobisisobutyronitrile; the high boiling point solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:2:3; the inert gas is argon.
[0043] The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding the copolymer into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 63°C, soaking for 23 hours, washing with clean water, and drying to prepare the functional synthetic fiber; the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 10wt%; the process parameters of the melt spinning are: spinning temperature of 225°C, winding speed of 1100m / min, and drafting multiple of 4.0.
[0044] The carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filaments, and is provided by Zhejiang Rifang Nanobiotechnology Co., Ltd.; the medical chitosan fiber has a thickness of 2D and a fiber shape of filaments, the brand is Yingjia Ke 100, the item number is CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0045] A preparation method of the antistatic medical gauze comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:29, first washing with 99°C water for 29 minutes, then lowering the temperature by 9°C and washing with water for 7.5 minutes; taking out the cloth, dehydrating it with a dehydrator for 24 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 130°C for 24 minutes to obtain the antistatic medical gauze.
[0046] Example 5
[0047] An antistatic medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, the medical chitosan fiber and the functional synthetic fiber is 0.4:0.5:0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer and 5 parts of (3,6-diamino-9-acridinyl)boric acid; the functional synthetic copolymer comprises The structural units introduced by the following monomers are included: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0048] The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting at 70°C for 6 hours in an inert gas atmosphere, then precipitating in water, washing the precipitated polymer with water for 6 times, and finally placing the polymer in a vacuum drying oven at 95°C. Dry to constant weight to obtain a functional synthetic copolymer; the mass ratio of the 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:3:1.2:2:0.3:0.08:30; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is nitrogen.
[0049] The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding the copolymer into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 65°C, soaking for 25 hours, washing with clean water, and drying to prepare the functional synthetic fiber; the mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 12wt%; the process parameters of the melt spinning are: spinning temperature of 230°C, winding speed of 1200m / min, and drafting multiple of 4.2.
[0050] The carbon nanotube graphene conductive fiber has a thickness of 300D and a fiber shape of filaments, and is provided by Zhejiang Rifang Nanobiotechnology Co., Ltd.; the medical chitosan fiber has a thickness of 2D and a fiber shape of filaments, the brand is Yingjia Ke 100, the item number is CSF100, and is provided by Weifang Yingke Marine Biomaterials Co., Ltd.
[0051] A preparation method of the antistatic medical gauze comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:30, first washing with 100°C water for 30 minutes, then lowering the temperature by 10°C and washing with water for 8 minutes; taking out the cloth, dehydrating it with a dehydrator for 25 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 132°C for 26 minutes to obtain the antistatic medical gauze.
[0052] Comparative Example 1
[0053] An antistatic medical gauze and a preparation method thereof are basically the same as those in Example 1, except that 1-allyl-3-methylimidazole chloride and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt are not added, and functional synthetic fibers are used instead of carbon nanotube graphene conductive fibers.
[0054] Comparative Example 2
[0055] An antistatic medical gauze and a preparation method thereof, which are basically the same as Example 1, except that (3,6-diamino-9-acridinyl)boric acid and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione are not added, and functional synthetic fibers are used instead of medical chitosan fibers.
[0056] In order to further illustrate the unexpected positive technical effects achieved by the products of each embodiment of the present invention, the antistatic medical gauze prepared in each example was tested for relevant properties. The test results are shown in Table 1. The test method is as follows:
[0057] (1) Antimicrobial property and antimicrobial stability: The test was conducted according to GB / T 20944.3-2008 Evaluation of antimicrobial properties of textiles Part 3: Oscillating bottle method. After 28 days, the antimicrobial property test was conducted again according to the above method. The test bacteria was Staphylococcus aureus.
[0058] (2) Air permeability: The gauze samples to be tested (area 2000mm 2 ) Tested by YG461H automatic air permeability instrument, the pressure difference is 100Pa, the test conditions are: temperature 20±2℃, humidity 65±2% constant temperature and humidity laboratory, the test reference standard is: GB / T5453-1997 "Determination of air permeability of fabrics".
[0059] (3) Antistatic performance evaluation: The antistatic medical gauze prepared in the examples was tested according to the national standard GB / T 12703.1-2008 "Evaluation of electrostatic properties of textiles Part 1: Static voltage and half-life", and the test conditions were: temperature 20°C, relative humidity 35%. The half-life (s) of the static voltage was used for evaluation. Three samples were tested for each group of examples, and the average value was taken.
[0060] Table 1
[0061]
[0062] As can be seen from Table 1, the antistatic medical gauze disclosed in the embodiment of the present invention has better antibacterial property, antibacterial stability, air permeability and antistatic property than the comparative example product, and the combined use of 1-allyl-3-methylimidazole chloride, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, functional synthetic fiber, carbon nanotube graphene conductive fiber, (3,6-diamino-9-acridinyl)boric acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and medical chitosan fiber is beneficial to improving the above properties.
[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as described above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. An antistatic medical gauze, characterized in that: The medical gauze is blended by carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber; the mass ratio of the carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber is 0.4:(0.3-0.5):0.6; the functional synthetic fiber is made of the following raw materials in parts by weight: 100 parts of functional synthetic copolymer and 3-5 parts of (3,6-diamino-9-acridinyl)boric acid; the functional synthetic copolymer includes The structural units introduced by the following monomers: 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; The preparation method of the functional synthetic fiber comprises the following steps: adding the functional synthetic copolymer into a melt spinning machine for melt spinning, then adding it into an aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid at 55-65° C., soaking for 15-25 hours, washing with clean water, and drying to prepare the functional synthetic fiber.
2. The antistatic medical gauze according to claim 1, characterized in that: The preparation method of the functional synthetic copolymer comprises the following steps: adding 1-allyl-3-methyl imidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium] propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl) methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and an initiator into a high boiling point solvent, stirring and reacting for 3-6 hours at 60-70°C in an inert gas atmosphere, then precipitating the polymer in water, washing the precipitated polymer with water for 3-6 times, and finally drying the polymer in a vacuum drying oven at 85-95°C to a constant weight to obtain the functional synthetic copolymer.
3. The antistatic medical gauze according to claim 2, characterized in that: The mass ratio of the 1-allyl-3-methylimidazole chloride, N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, N-(4-cyano-3-trifluoromethylphenyl)methacrylamide, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, initiator, and high boiling point solvent is 1:(1-3):(0.8-1.2):(1-2):(0.1-0.3):(0.05-0.08):(15-30).
4. The antistatic medical gauze according to claim 2, characterized in that: The initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
5. The antistatic medical gauze according to claim 1, characterized in that: The mass percentage concentration of the aqueous dispersion containing (3,6-diamino-9-acridinyl)boric acid is 5-12 wt %.
6. The antistatic medical gauze according to claim 1, characterized in that: The process parameters of the melt spinning are: spinning temperature 210-230° C., winding speed 500-1200 m / min, and drafting multiple 3.2-4.
2.
7. The antistatic medical gauze according to claim 1, characterized in that: The thickness of the carbon nanotube graphene conductive fiber is 300D, and the fiber shape is a filament; the thickness of the medical chitosan fiber is 2D, and the fiber shape is a filament.
8. A method for preparing the antistatic medical gauze according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: blending carbon nanotube graphene conductive fiber, medical chitosan fiber and functional synthetic fiber to form gauze grey cloth, then immersing the woven gauze grey cloth in a hot water tank of a descaling, boiling and bleaching combined machine at a bath ratio of 1:(25-30), first washing with water at 95-100 DEG C for 20-30 minutes, then lowering the temperature by 5-10 DEG C and washing with water for 4-8 minutes; taking out the cloth, dehydrating it with a dehydrator for 20-25 minutes; then opening the dehydrated grey cloth with a width opening machine, and then drying it with a drying machine at 108-132 DEG C for 16-26 minutes to obtain the antistatic medical gauze.
Citation Information
Patent Citations
A type of antistatic, alcohol-resistant, and plasma-resistant medical nonwoven fabric
CN113699788B
Antibacterial and antistatic fabric and preparation method thereof
CN113293480A
FRP profile composite material and preparation method thereof
CN115558231A